Preparation and characterization of sulfonated polystyrene/magnetite nanocomposites for organic dye adsorption - A.M. Al-Sabagh; Y.M. Moustafa; A. Hamdy; H.M. Killa; R.T.M. Ghanem; R.E. Morsi (Egyptian Journal of Petroleum)
Magnetite nanoparticles (MNPs) were prepared by co-precipitation method and were found to have average size of 5 nm with spherical shape crystalline structure with super-magnetic properties. Commercial polystyrene (PS) was sulfonated through the reaction with freshly prepared acetyl sulfate. Three different degrees of sulfonation, based on the ratio of the acetyl sulfate to polystyrene, were prepared (1:1, 1:3 and 1:5). Nanocomposites of the prepared magnetite nanoparticles 1:3 sulfonated polystyrene were prepared at different magnetite content (1, 5 and 10%). The produced materials were characterized by dynamic light scattering (DLS), transmittance electron microscope (TEM) X-ray diffraction (XRD) and vibrating sample magnetometer (VSM). PS, MNPs and the prepared nanocomposites were investigated as adsorbents for Congo Red (CR). The variables influencing the adsorption capacity, such as solution pH, contact time and the initial dye concentration were systematically investigated. The adsorption for CR by the previous adsorbents show maximum experimental uptake capacity of 26.78, 33.15, 53.35, 64.73, and 76.29 mg/g for PS, MNPs, SPS/MNPs 1%, SPS/MNPs 5% and SPS/MNPs 10%, respectively. The adsorption process was found to follow the pseudo second order kinetic model and fit quite well with Langmuir adsorption isotherm. Keywords: Polystyrene, Sulfonated polystyrene, Magnetite nanoparticles, Magnetite nanocomposites, Water decolorization, CR dye removal